Natural Fibers Towards Fashion Sustainability: A Review of Raw Materials, Production, Application, and Perspective - Tarikul Islam; Md Monir Hossain; Sha’Mira Covington (Journal of Natural Fibers)
Sustainability is becoming crucial for the survival of the fashion industry, with fiber, materials, and product innovations leading the way. Recently, the industry has embraced eco-friendly practices by using natural fibers in clothing and accessories. These fibers reduce environmental impact and represent a growing trend in sustainable fashion. Global production of natural fibers is expanding to meet increasing demand, gradually replacing synthetic and energy-intensive materials. This shift is driven by environmental awareness and the desirable qualities of natural fibers, such as lightweight and cost-effectiveness. This study aims to thoroughly review the most commercially important natural fibers, exploring their production, applications in sustainable fashion, properties, and industry cost considerations. The synthesis of a broad range of information into a cohesive analysis makes the review a valuable contribution to the discourse on sustainable fashion.